Design of Ijarah Sukuk - Rohmatunnisa, Dinna (2008)
ABSTRACT Compared to conventional bonds and total financial assets, the share of Islamic bonds is very small. However, since 2002 the issuance of this instrument has increased rapidly and it is expected to keep increasing in the future. The purpose of the dissertation is to discuss on Ijarah sukuk pricing, and on a review of the literature concerning Shariah and financial issues related to the instrument, as a basis to construct a financial model to price it. To build the formula for the Ijarah sukuk, three types of model are used: the model for leasing as illustrated by Schallheim (1994), McConnell and Schallheim (1983) and Myers, Dill and Bautista (1976); the formal mortgage system as illustrated by Ebrahim and Ahmed (2008), and the cost of capital in a non-interest economy by Mirakhor (1996). From the analysis of the above pricing model and also from review of Shariah and financial issues related to the instrument, it is concluded that the pricing of Ijarah sukuk is an analogy of conventional bond price with some adjustments such as the presence of SPV (Special Purpose Vehicle) fee, Legal and Shariah boards' fee, and operating expenses. This dissertation illustrates four types of formula based on the conditions in the contract, such as the Ijarah sukuk with (1) repurchase transaction held with certainty and with a predetermined price (2) repurchase transaction with certainty and the asset price follows geometric Brownian motion (gBm), (3) repurchase transaction with call option and with predetermined price, (4) repurchase transaction with call option and the asset price follows geometric Brownian motion (gBm).